Pre-service Teachers’ Decision-Making and Classroom Assessment Practices - Oo, Cherry Zin; Alonzo, Dennis; Davison, Chris (Frontiers in Education, 2021)
Classroom assessment practices play a pivotal role in ensuring effective learning and teaching. One of the most desired attributes of teachers is the ability to gather and analyze assessment data to make trustworthy decisions leading to supporting student learning. However, this ability is often underdeveloped for a variety of reasons, including reports that teachers are overwhelmed by the complex process of data analysis and decision-making and that often there is insufficient attention to authentic assessment practices which focus on assessment for learning (AfL) in initial teacher education (ITE), so teachers are uncertain how to integrate assessment into teaching and make trustworthy assessment decisions to develop student learning. This paper reports on the results of a study of the process of pre-service teachers’ (PSTs) decision-making in assessment practices in Myanmar with real students and in real classroom conditions through the lens of teacher agency. Using a design-based research methodology, a needs-based professional development program for PSTs’ assessment literacy was developed and delivered in one university. Following the program, thirty PSTs in the intervention group were encouraged to implement selected assessment strategies during their practicum. Semi-structured individual interviews were undertaken with the intervention group before and after their practicum in schools. This data was analyzed together with data collected during their practicum, including lesson plans, observation checklists and audiotapes of lessons. The analysis showed that PSTs’ decision-making in the classroom was largely influenced by their beliefs of and values in using assessment strategies but, importantly, constrained by their supervising teachers. The PSTs who understood the principles of AfL and wanted to implement on-going assessment experienced tension with supervising teachers who wanted to retain high control of the practicum. As a result, most PSTs could not use assessment strategies effectively to inform their decisions about learning and teaching activities. Those PSTs who were allowed greater autonomy during their practicum and understood AfL assessment strategies had greater freedom to experiment, which allowed them multiple opportunities to apply the result of any assessment activity to improve both their own teaching and students’ learning. The paper concludes with a discussion of the kind of support PSTs need to develop their assessment decision-making knowledge and skills during their practicum.